2013
DOI: 10.1016/j.ejphar.2013.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Rapid human melanoma cell death induced by sanguinarine through oxidative stress

Abstract: Sanguinarine is a natural isoquinoline alkaloid derived from the root of Sanguinaria canadensis and from other poppy fumaria species, and is known to have a broad spectrum of pharmacological properties. Here we have found that sanguinarine, at low micromolar concentrations, showed a remarkably rapid killing activity against human melanoma cells. Time-lapse videomicroscopy showed rapid morphological changes compatible with an apoptotic cell death, which was further supported by biochemical markers, including ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Consistently, pre-treatment of tumor cells with antioxidants such as N-acetylcysteine or glutathione counteracts the apoptosis induced by sanguinarine [21,32,37,52] . Moreover, the over-expression of cyclooxygenase-2 (COX-2) also rescues prostate cancer cells from sanguinarine-induced apoptosis by sanguinarine enhances apoptosis in human mammary adenocarcinoma MCF-7 through the inhibition of VEGF release, induced by generation of ROS [32] .…”
Section: Sanguinarine-induced Apoptosis Through the Generation Of Reamentioning
confidence: 75%
See 2 more Smart Citations
“…Consistently, pre-treatment of tumor cells with antioxidants such as N-acetylcysteine or glutathione counteracts the apoptosis induced by sanguinarine [21,32,37,52] . Moreover, the over-expression of cyclooxygenase-2 (COX-2) also rescues prostate cancer cells from sanguinarine-induced apoptosis by sanguinarine enhances apoptosis in human mammary adenocarcinoma MCF-7 through the inhibition of VEGF release, induced by generation of ROS [32] .…”
Section: Sanguinarine-induced Apoptosis Through the Generation Of Reamentioning
confidence: 75%
“…Moreover, an overdone oxidative stress has been shown capable of inducing a reduction of the normal mitochondrial membrane potential, which in turn leads to apoptosis [21,[61][62][63] . It has been shown that ROS generation, is crucial for the apoptosis induced by sanguinarine in human breast cancer [52] , SK-Mel-2 human melanoma [37] , human prostate cancer [25] and in both HCT-116 [21] and HT-29…”
Section: Sanguinarine-induced Apoptosis Through the Generation Of Reamentioning
confidence: 99%
See 1 more Smart Citation
“…The antiproliferative and/or pro-apoptotic activities of sanguinarine have been demonstrated in cells derived from several human cancers including epidermal (Ahmad et al, 2000), keratinocytes (Adhami et al, 2003;Reagan-Shaw et al, 2006), prostate (Malikova et al, 2006b;Adhami et al, 2004;Huh et al, 2006), cervical (Ding et al, 2002), breast Debiton et al, 2003;Holy et al, 2006), leukemia (Han et al, 2008;Weerasinghe et al, 2001c;Weerasinghe et al, 2001b;Weerasinghe et al, 2001a), lymphoma (Hussain et al, 2007), melanoma (Burgeiro et al, 2013;Hammerova et al, 2011;Serafim et al, 2008), colon (Lee et al, 2012;Matkar et al, 2008), colorectal (Han et al, 2013a;Lee et al, 2012;Pica et al, 2012), gastric (Choi et al, 2009), pancreatic (Ahsan et al, 2007), lung (Jang et al, 2009), neuroendocrine (Larsson et al, 2010), osteosarcoma (Park et al, 2010), and in rat glioblastoma cells (Han et al, 2007), bladde (Han et al, 2013b). However, the impact of sanguinarine on neuroblastoma cells has not been shown.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, extracted polysaccharides from certain edible mushrooms can cause cancer cell apoptosis in vitro by generating high level of mitochondrial ROS [60]. Other plant-derived environmental factors, such as sanguinarine and herbacetin, also are potent inducers of human cancer cell death via the ROS-mediated mitochondrial apoptotic pathway [61,62]. Finally, some environmental agents that are known to be toxic may also have beneficial effects in the aspect of inhibiting cancer cell growth.…”
Section: Environment Factors That Act On Mitochondriamentioning
confidence: 99%